Glycerol Steam Reforming Over Ni-Fe-Ce/Al2O3 Catalyst: Effect of Cerium - Go, Gwang-Sub; Go, Yoo-Jin; Lee, Hong-Joo; Moon, Dong-Ju; Park, Nam-Cook; Kim, Young-Chul (AMER SCIENTIFIC PUBLISHERS, 2016)
In this work, hydrogen production from glycerol by steam reforming was studied using Ni-metal oxide catalysts. Ni-based catalyst becomes deactivated during steam reforming reactions because of coke deposits and sintering. Therefore, the aim of this study was to reduce carbon deposits and sintering on the catalyst surface by adding a promoter. Ni-metal oxide catalysts supported on Al2O3 were prepared via impregnation method, and the calcined catalyst was reduced under H-2 flow for 2 h prior to the reaction. The characteristics of the catalysts were examined by XRD, TPR, TGA, and SEM. The Ni-Fe-Ce/Al2O3 catalyst, which contained less than 2 wt% Ce, showed the highest hydrogen selectivity and glycerol conversion. Further analysis of the catalysts revealed that the Ni-Fe-Ce/Al2O3 catalyst required a lower reduction temperature and produced minimum carbon deposit.
Keywords: HYDROGEN-PRODUCTION